Growth and spatial distribution of nutrient-absorbing organs: selective exploitation of soil heterogeneity - John, T.V.St.; Coleman, D.C.; Reid, C.P.P.
The soil is a heterogeneous medium with respect to decomposition activity and consequently with respect to nutrient availability. Roots of forest trees and hyphae of vesiculararbuscular mycorrhizal (VAM)fungi, principal nutrient absorbing organs, have previously been observed to associate with decomposing organic matter and other localized sites of nutrient availability in the soil. In two experiments in forests on contrasting soil types in Brazilian Amazonia, the association of tree roots with decomposing organic matter was shown to be a response of new root growth in the organic matter, not an avoidance of unfavorable conditions elsewhere in the soil volume. In laboratory experiments, the growth of VAM fungal hyphae was shown to respond to particles of decomposing organic matter in a way analogous to the response of forest tree roots. In both cases localized nutrient-rich sites (organic matter)were encountered by random growth of individual roots (hyphae)followed by increased branching after the encounter. Length of roots (and probably of hyphae)followed the negative binomial distribution, which is also found in other spatially aggregated organisms in heterogeneous environments. Although roots and hyphae operate in different size scales, the selective exploitation of localized nutrient-rich sites and the mechanism by which the advantageous physical placement comes about is strikingly similar. The highly branched roots and hyphae in association with decomposing organic matter should be advantageous when ion uptake is limited by either diffusion rate or competition with other organisms.
Keywords: EXTRAMATRICAL MYCELIUM; HYPHAL GROWTH; NEGATIVE BINOMIAL DISTRIBUTION; ROOT GROWTH; SOIL HETEROGENEITY; TROPICAL FOREST; VESICULAR-ARBUSCULAR MYCORRHIZAE